When the Easy Becomes Difficult: Factors Affecting the Acquisition of the English /iː/-/ɪ/ Contrast - Cebrian, Juli; Gorba, Celia; Gavaldà, Núria (Frontiers in Communication, 2021)
The degree of similarity between the sounds of a speaker’s first and second language (L1 and L2) is believed to determine the likelihood of accurate perception and production of the L2 sounds. This paper explores the relationship between cross-linguistic similarity and the perception and production of a subset of English vowels, including the highly productive /iː/-/ɪ/ contrast (as in “beat” vs. “bit”), by a group of Spanish/Catalan native speakers learning English as an L2. The learners’ ability to identify, discriminate and produce the English vowels accurately was contrasted with their cross-linguistic perceived similarity judgements. The results showed that L2 perception and production accuracy was not always predicted from patterns of cross-language similarity, particularly regarding the difficulty distinguishing /iː/ and /ɪ/. Possible explanations may involve the way the L2 /iː/ and /ɪ/ categories interact, the effect of non-native acoustic cue reliance, and the roles of orthography and language instruction.